Strategic Ecological Issues: Environmental Problems in a Perspective of Regional Development in Bangka Belitung - Haryadi Dwi; Ibrahim Ibrahim; Darwance Darwance (E3S Web of Conferences, 2021)
A region’s development planning should be carried out by referring to the strategic issues faced by the region. Thus, strategic issues become the basis upon which regional governments formulate their policies and work programs. This study examined how each region in Bangka Belitung Islands Province positioned strategic issues of ecology in its regional development planning. The current writers examined eight regional governments’ Regional Medium-Term Development Plan (RMTDP) documents; one of which belongs to the provincial government, while the rest belongs to the regency/city governments. This study found that ecological issues comprised an average 17.6% of the strategic issues in all of the planning documents, the highest of which was found in Belitung Regency’s planning document. In addition, the analysis revealed that the general focus of the strategic ecological issues was environmental damage, which was reported by three of the regions as a result of mining activities. This study provides an illustration of how each regional government is committed to take ecological issues seriously and include them in the strategic issues at the regional level.